Utilization of SPOT Image for Settlement Quality Study in Tanjung Harapan District, Solok City - Trisna Dwi Yuliana (Remote Sensing Technology Study Program, 2020)
Tanjung Harapan District is the district with the highest population density, which is 1,223 people/km². Thus the total population of the number of residential areas increased. This increase in population has had an impact on increasing the need for land for housing, thus affecting the quality of settlements. This study aims to determine the level of quality of settlements in Tanjung Harapan District, Solok City. The method used is weighting (scoring) and Overlay to combine all settlement quality parameters. The results obtained are a map of the quality level of settlements in Tanjung Harapan District which has three classifications, namely good class with an area of ​​74 Ha, medium class with an area of ​​69 Ha, and bad class with an area of ​​83 Ha.